PENERAPAN KATA BAKU DALAM PEMBELAJARAN BAHASA INDONESIA MENGGUNAKAN MEDIA APK. BAKU VS TIDAK BAKU DI KELAS IV UPT SD NEGERI 53 GRESIK - Yunita Alfiyanti; Nanang Khoirul Umam (STKIP Subang, 2022)
ABSTRACT Understanding standard words in a language can be taught at the elementary school level. This is the importance of understanding standard Indonesian words through technology; this is part of the reason why better languages ​​are standard languages. This study aims to improve students' Indonesian vocabulary through technology. This study shows how students of UPT SD NEGERI 53 GRESIK do not understand standard words. They also show no particular application to understanding standard words. The data for this study were collected through observation and interview techniques. In everyday life, students often need to communicate using mixed languages. This is one of the many reasons why so many factors come into play. Adding standard words into their daily communication still uses discussion and lecture methods. This makes it difficult for students to understand standard words. Standard words play a key role in this academic research. In particular, standard English vocabulary is applied to Indonesian through technological means. This includes the use of language applications. The lack of learning to communicate effectively in school through standard words is shown in this study. The teacher's habit of understanding standard words is rarely broken. This causes a lack of awareness of the importance of using standard words in schools. Keywords: Learning, Standard Word, Media Application